Efektifitas terapi dzikir terhadap tingkat depresi pada lansia : kajian literatur - Saputri, Sindika Aprilia; Supratman, Supratman (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Individuals who are in the final stages of human life are referred to as elderly (senior age). As they age, the elderly tend to experience decreased muscle strength, bone density, and a weakened immune system, making them more susceptible to various degenerative diseases such as osteoporosis, hypertension, diabetes, and heart disease. Dhikr is a form of non-pharmacological therapy that can help reduce the anxiety experienced. This therapy is carried out by reciting dhikr verbally, which can create feelings of happiness and relaxation, thereby reducing the pain felt. Purpose: To determine the effectiveness of dhikr therapy on depression levels in the elderly. Methods: The analysis in this article is done descriptively by referring to relevant articles. Source searches are carried out through electronic databases, namely Google Scholar and Garuda, with a publication period between 2022 and 2025 and as many as three articles reviewed in this study using the PRISMA standard. Results: The analysis in this article is done descriptively by referring to relevant articles. Source searches are carried out through electronic databases, namely Google Scholar and Garuda, with a publication period between 2022 and 2025 and as many as three articles reviewed in this study using the PRISMA standard. Conclusion: Analysis shows that dhikr therapy can significantly reduce anxiety levels in the elderly. Suggest: Social institutions and the Elderly Service Center are advised to integrate dhikr therapy into mental welfare programs for the elderly. Keywords: Anxiety; Dhikr Therapy; Elderly Pendahuluan: Individu yang berada pada tahap akhir kehidupan manusia disebut sebagai lansia (lanjut usia). Seiring bertambahnya usia, lansia cenderung mengalami penurunan kekuatan otot, kepadatan tulang, serta melemahnya sistem imun, sehingga lebih rentan terhadap berbagai penyakit degeneratif seperti osteoporosis, hipertensi, diabetes, dan penyakit jantung. Dzikir merupakan salah satu bentuk terapi non-farmakologis yang dapat membantu mengurangi rasa cemas yang dialami. Terapi ini dilakukan dengan melafalkan dzikir secara lisan, yang dapat menciptakan perasaan bahagia dan rileks, sehingga mengurangi rasa sakit yang dirasakan. Tujuan: Untuk mengetahui Efektivitas terapi dzikir terhadap tingkat depresi pada lansia. Metode: Analisis dalam artikel ini dilakukan secara deskriptif dengan merujuk pada artikel-artikel yang relevan. Penelusuran sumber dilakukan melalui database elektronik, yaitu Google Scholar dan Garuda, dengan rentang waktu publikasi antara tahun 2022 hingga 2025 dan sebanyak tiga artikel yang dikaji dalam penelitian ini menggunakan standar PRISMA. Hasil: Analisis menunjukkan bahwa terapi dzikir secara signifikan dapat menurunkan tingkat kecemasan pada lansia. Saran: Lembaga sosial dan Balai Pelayanan Tresna Werdha disarankan untuk mengintegrasikan terapi dzikir dalam program kesejahteraan mental bagi lansia. Kata Kunci : Kecemasan; Lansia; Terapi Dzikir